2017
DOI: 10.4236/pp.2017.82003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peptidase Inhibitors on Dynorphin A (1-17) or (1-13)-Induced Antinociception and Toxicity at Spinal Level

Abstract: Our group has earlier demonstrated that three enzymes sensitive to peptidase inhibitors (PIs), amastatin (A)-, captopril (C)-, and phosphoramidon (P), played an important role in inactivation of enkephalins at the spinal level. Dynorphin-converting enzyme (DCE) hydrolyzes dynorphin (Dyn) A (1-17) or Dyn A (1-13) mainly at the Arg 6 -Arg 7 bond. Dynorphin A and its derived peptides interact with opioid and glutamate receptors at their N-and C-terminals, respectively. The purpose of the present study was to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…High-dose administration of opioids can lead to lethal toxicity in multiple organ systems (Boyer, 2012). Earlier studies by the present group revealed that administration of a mixture of PIs enhanced antinociception induced by low-dose administration of dynorphin without toxicity (Ajimi et al, 2015;Matsuda et al, 2017). These results demonstrated that the use of PIs synergizes and potentiates intrinsic signaling pathways, which would allow a reduction in the doses required and subsequent avoidance of toxicity.…”
Section: Downloaded Fromsupporting
confidence: 55%
See 1 more Smart Citation
“…High-dose administration of opioids can lead to lethal toxicity in multiple organ systems (Boyer, 2012). Earlier studies by the present group revealed that administration of a mixture of PIs enhanced antinociception induced by low-dose administration of dynorphin without toxicity (Ajimi et al, 2015;Matsuda et al, 2017). These results demonstrated that the use of PIs synergizes and potentiates intrinsic signaling pathways, which would allow a reduction in the doses required and subsequent avoidance of toxicity.…”
Section: Downloaded Fromsupporting
confidence: 55%
“…accordance with the method in earlier studies by the present group (Kitamura et al, 2000;Takahashi et al, 2007;Akahori et al, 2008;Murata et al, 2014;Ajimi et al, 2015;Matsuda et al, 2017), nociceptive stimulation was achieved by immersing the tail of each rat in hot water (55ºC) for a maximum of 5 sec. This time limit was set to prevent injury to the animal in accordance with the result from earlier studies by the present group showing that persistent pain occurs when the tail is placed in hot water for more than 5 seconds (data not shown).…”
Section: Downloaded Frommentioning
confidence: 99%